Biomarkers in Barrett’s Esophagus - Mesquita, Marta Catarina da Piedade Sirgado (2020)
Barrett’s esophagus (BE) is a recognized premalignant condition of the distal esophagus that constitutes the major risk factor for the development of esophageal adenocarcinoma (EA). Despite the known low rates of BE progression to EA, the incidence of both has increased profoundly over the last decades and esophageal malignancy remains to be a deadly cancer with high morbidity and mortality unless diagnosed at early stages. Current BE clinical management has revealed unsuccessful in reverting this worrisome epidemiological picture and a major hurdle has been the incapacity to discriminate among BE patients those who have a higher risk of malignant progression. In fact, to this date, besides dysplasia none of the existing clinical and histologic criteria could anticipate malignant progression. It is therefore imperative to find reliable molecular biomarkers to guide medical practice and improve the standard of care for BE patients. The global aim of this thesis was to better understand the pathways underlying BE malignant progression and thereby identify reliable biomarkers relevant for the diagnosis, prognosis and management of BE patients thus contributing to an improved understanding of BE biology and an optimized support for clinical decisions. To accomplish these challenging goals an unbiased and a hypothesis-driven strategies were followed. Through the unbiased approach, a meta-analysis of transcriptome datasets and subsequent experimental validation in a cohort BE patients in follow-up was used to define a gene set associated with BE cancer development and, therefore, identify early biomarkers predictive of BE malignant progression. In silico analysis singled out two genes, CYR61 and TAZ as candidate predictive markers for BE malignant progression and experimental validation using quantitative PCR and immunohistochemistry revealed that both genes are upregulated and overexpressed in non-dysplastic BE index biopsies from progressors years before cancer development when compared with index biopsies from BE patients that did not progressed. We also found that EMT and stemness-related genes were also significantly over represented in BE associated with progression. Together, these results support that CYR61 and TAZ are promising early biomarkers to stratify BE patients according to their cancer risk and suggest a novel mechanist route for BE neoplastic progression. Using an hypothesis-driven approach, we explored when and how centrosome abnormalities arise along BE malignant pathway, from the early premalignant condition stage to metastatic disease, by establishing an accurate method to identify and score centrosomes, at the single-cell level, in patient samples and cell lines. We found that centrosome amplification arises as early as the premalignant condition of patients that progress to malignancy and significantly expands at dysplasia stage, which is dependent of p53 loss of function, being then present along cancer progression, namely in EA and metastasis. So, these finding suggest that centrosome amplification could contribute to BE initiation and malignant progression. Considering that centrosome amplification is specific of patients that progress to cancer, this could be further explored to be translated into useful tools to be used in the clinical setting and potentially improve its diagnosis, prognosis and treatment. Moreover, given widespread occurrence of both p53 mutations and centrosome abnormalities in human tumors, our findings are likely to be extended to other cancers. Collectively, both research avenues suggest the existence of different cellular and molecular abnormalities dictating different pathological propensity for malignant progression in BE, right from the beginning, and this could be further explored to trace a cancer risk profile for every patient and guide medical decisions and improve patient care.